Configuration design and simulation of the six-legged robot with bouncing characteristics - WANG Jiaju; ZHUANG Hongchao; ZHANG Zeyu; WANG Kai (Jixie chuandong)
ObjectiveTo address the issue of poor adaptability to the unstructured terrain in mobile systems, a six-legged robot with bouncing characteristics was proposed, and the overall configuration and individual legs of the robot were structurally designed.MethodsA comparison was made between the crawling characteristics of multi-legged spiders and caterpillars, and a six-legged evenly distributed leg arrangement was adopted for the robot legs. To achieve jumping functionality, a leg energy storage mechanism was designed. The various parts of the six-legged robot were drawn using SolidWorks three-dimensional drawing software to assemble a virtual prototype. A single-leg motion coordinate system was established, and forward and inverse kinematic analyses were conducted using the D-H method. The motion modes under static and dynamic gaits were discussed, and simulation validation was performed using Adams software.ResultsThe results demonstrate that the configuration design and gait planning of the six-legged robot are reasonable, providing reference for further research.